Anterior and Posterior Serape: The Rotational Core - Santana, J. C.; McGill, S. M.; Brown, L. E. (Strength and Conditioning Journal, 2015)
The purpose of this article is to expand a concept surrounding the rotational function and training of the body's core. more than a decade ago, a model was provided by which to observe and train the core, which was based on a previously published theory regarding the serape effect. the purpose of this article is to expand on that model, the original serape effect, and to provide a more complete model for analysis and training of the body's core.